Insights on the Quest for the Structure–Function Relationship of the Mitochondrial Pyruvate Carrier - José Edwin Neciosup Quesñay (Biology, 2020)
The molecular identity of the mitochondrial pyruvate carrier (MPC) was presented in 2012, forty years after the active transport of cytosolic pyruvate into the mitochondrial matrix was first demonstrated. An impressive amount of in vivo and in vitro studies has since revealed an unexpected interplay between one, two, or even three protein subunits defining different functional MPC assemblies in a metabolic-specific context. These have clear implications in cell homeostasis and disease, and on the development of future therapies. Despite intensive efforts by different research groups using state-of-the-art computational tools and experimental techniques, MPCs’ structure-based mechanism remains elusive. Here, we review the current state of knowledge concerning MPCs’ molecular structures by examining both earlier and recent studies and presenting novel data to identify the regulatory, structural, and core transport activities to each of the known MPC subunits. We also discuss the potential application of cryogenic electron microscopy (cryo-EM) studies of MPC reconstituted into nanodiscs of synthetic copolymers for solving human MPC2.